PERAMALAN PROFITABILITAS PERBANKAN SYARIAH INDONESIA: STUDI BANK RAKYAT INDONESIA SYARIAH PRA MERGER TAHUN 2010-2020 - Adi Sopian; Risfiana Mayangsari; Siti Rohmat; Lilis Sulastri (Komitmen: Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the performance of return on assets, the ratio of operating expenses to operating income, return on equity, and non-performance Financings in the next 10 years. This research method uses a quantitative descriptive method to predict the growth of Islamic banking profitability. The population and sample used in the pre-merger study of Bank Rakyat Indonesia Syariah. The data used is financial reports for ROA values every year from 2010-2020. The research results show that there has been a decline in the profitability of Bank Rakyat Indonesia Syariah. This is shown by the prediction of a decrease in ROA, BOPO, ROE and NPF. The decision to merge with Bank Syariah Indonesia was the right decision because it can be seen from the growth rate of BRIS' profitability that tends to decrease every year.